Climate resilience : how we keep each other safe, care for our communities, and fight back against climate change - Flanagan, Kylie (North Atlantic Books, 2023)
"A primer in understanding the climate crisis informed by interviews with the women, non-binary, and gender-expansive climate leaders and community members who have been fighting for the health, wellbeing, and liberation of their communities for decades"--